How have sanctions impacted Russia? - Maria Demertzis; Benjamin Hilgenstock; Ben McWilliams; Elina Ribakova; Simone Tagliapietra (Bruegel, 2022)
Russia's invasion of Ukraine has triggered a series of sanctions imposed by the European Union, the United States and others. Sanctions included restrictions on Russia's financial industry, its central bank and its coal and oil exporters, in addition to general export controls. Meanwhile, foreign companies have withdrawn voluntarily from the Russian market as a result of a 'self-sanctioning' trend. We assess the impact these sanctions have had on Russia's economy in the immediate aftermath of the invasion and more structurally. Russian fiscal revenues have not suffered from sanctions sufficiently to reduce the length of this war. Effective management by the Bank of Russia has prevented financial instability and has therefore also protected the real economy. However, this picture of economic containment is coming to an end. Russia's fiscal revenues are now beginning to take a hit; given the breadth of sanctions, the economy will suffer in the medium to long term. The voluntary departure of a large number of western firms, eventual energy decoupling by the EU and Russia's inability to find equal alternatives will damage the Russian economy severely. As the Russian economy closes in on itself, it will become harder to find reliable data to evaluate the extent of the hit. Still greater sanctions coordination across the globe is needed to isolate the Russian economy, limit the flow of income into Russian coffers and therefore help stop the war.
Keywords: 330